Dismenorea, Akupresur, Sosialisasi dan Pelatihan Fintech bagi Pedagang UKM di Pasar Kebayoran Lama - Astri Rumondang Banjarnahor (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The development of financial technology (fintech) has significantly impacted various economic sectors, including traditional markets. Despite many conventional market traders still relying on cash transactions and having limited access to banking systems, implementing fintech has the potential to improve access to capital and operational efficiency. This article discusses the socialization and training of fintech held at Kebayoran Lama Market, South Jakarta, aiming to enhance traders' understanding of using fintech for business capital access. Through initial surveys, socialization, and practical training, traders were taught about digital payments, peer-to-peer (P2P) lending, and financial management applications. The results showed increased traders' understanding of fintech, although there are still barriers related to device limitations and internet access. The article also identifies solutions to improve the sustainability of fintech usage in traditional markets, including government support and collaboration with fintech providers.